Salivary IL-33 and sST2 levels in relation to TLR2 rs111200466 polymorphism and periodontitis - Yilmaz Mustafa; He Qiushui; Demir Esra; Teräsjärvi Johanna; Gursoy Ulvi Kahraman (WILEY, 2025)
Objectives: Toll-like receptor-2 (TLR2) signalling pathway is involved in the regulation of interleukin (IL)-33 and its receptor suppression of tumorigenicity-2 (ST2). This study aimed to compare salivary IL-33 and soluble ST2 (sST2) levels of periodontitis patients with those of periodontally healthy individuals in relation to their TLR2 rs111200466 23-bp insertion/deletion polymorphism within the promoter region.Materials and
Methods: Unstimulated saliva samples were collected, and periodontal parameters were recorded from 35 periodontally healthy individuals and 44 periodontitis patients. Non-surgical treatments were applied to periodontitis patients, and sample collections and clinical measurements were repeated 3 months following therapy. Salivary IL-33 and sST2 levels were measured with enzyme-linked immunosorbent assay kits, and TLR2 rs111200466 polymorphism was detected by polymerase chain reaction.
Results: Elevated salivary IL-33 (p = 0.007) and sST2 (p = 0.020) levels were observed in periodontitis patients, in comparison to controls. sST2 levels declined 3-months following treatment (p < 0.001). Increased salivary IL-33 and sST2 levels were found to be associated with periodontitis, with no significant relation to the TLR2 polymorphism.
Conclusion: Periodontitis, but not TLR2 rs111200466 polymorphism, is associated with elevated salivary sST2 and possibly IL-33 levels, and periodontal treatment is effective in reducing salivary sST2 levels.